La imagen del gaucho argentino en los primeros films de dibujos animados estadounidenses - Ana Teresa Fanchin (Les Cahiers ALHIM)
This contribution analyzes films produced by Disney, which top the list of comics displayed on celluloid. This particular source of cartoons, exhibited on the screen and that would reach wide dissemination, has to illustrate the representation of the gaucho of the Argentine pampas by the estadounidense vision, in instances that aspired to achieve its world hegemony. At the same time, because these projections were intended mainly for the child population, the conception of childhood at the time and the generation of recreational spaces are considered, not only as areas of socialization, but as facilitators of the transmission of cultural principles and values.